ASSESSMENT OF AGROECOLOGICAL STATE OF ARABLE LANDS OF FOREST-STEPPE ZONE OF RIVNE REGION - Klуmenko Mykola; Klуmenko Oleksandr; Dolzhenchuk, Viktor; Onyshchuk, Nataliia (Вісник Національного університету водного господарства та природокористування. Серія «Сільськогосподарські науки», 2020)
Assessment of agroecological state of arable lands of forest-steppe zone of Нoshcha district, Symoniv Village Council was carried out. Agroecological state of forest-steppe arable lands has undergone essential changes for the forty-five year period of their exploitation. These changes can be divided into three periods: the first one (between 1965 to 1990) – the growth of their fertility level, the second (between 1990 to 1995) – relatively stable level of fertility, and the third (between 1996 to 2010) – gradual decrease of their fertility. According to complex estimаtion of agroecological state prevailing majority of forest-steppe areas of Rivne region are referred to category unsufficiently fit for formation there special raw zones with integrated index randing from 0,40 to 0,49 and arable lands of Нoshcha region are qualified as unsufficiently fit (0,44-0,47) and partly unfit (0,20-0,38). It is ascertained that arable lands of Symoniv Village Council according to integrated agroecological index within the period between 2001 to 2005 are estimated as the category of unsufficiently fit (0,58) and within the period between 2016 to 2020 as unfit (0,35).